A Community Based Study on the Attitude of Family towards Elderly, Girl Child Education, Nutrition and Health Care in the Rural Field Practice Areas of a Tertiary Care Hospital in Mangalore - Krishna, Narayana Venkatesh; Louis Palatty, Princy; Suresh, Sucharitha (Journal of Pharmacy Practice and Community Medicine)
Introduction: The rural population is consistently less well off than the urban population with respect to health. Rural residents often experience barriers to health care that limit their ability to obtain the care they need. Therefore, sufficient healthcare access, necessary and appropriate services must be available in timely manner. This study helps us in knowing how people in rural and urban areas are dealing with their health, their attitude towards the elderly people and importance of girl child education, nutrition and health care. Objectives: 1. To know the attitude of the people towards the geriatric age group and also towards the girl child education, nutrition and health care. 2. To study the opinion of the people regarding the different systems of medicine and their preferences between the public and private healthcare and also their views on the satisfaction of treatment which they received. Methodology: It is a cross – sectional, descriptive, questionnaire-based study. A Community based study was conducted in the rural field practice areas of Department of Community Medicine, Father Muller Medical College, Mangalore, Karnataka, India between 25.09.2017 to 5.10.2017. The sample size was calculated using the purposive sampling technique. About 227 questionnaires were used to interview the subjects. Results: 191(84.1%) of people told that the elderly were not a burden financially or physically and 190(83.07%) told they were not a burden mentally. 215(94.7%) agreed about the girl child education and health care and 217(97.7%) told that same food was served to men and women in their families. 210(92.5%) believed in modern medicine, 151(66.5%) preferred private doctors and 214(94.3%) of people were satisfied with the treatment they received. Conclusion: Majority of the elderly are looked after well and not considered as a burden. Equal importance is given to the girl child education, nutrition and health care. Most of the people believed in the modern system of medicine, preferred the private doctors for treatment and also were satisfied with the treatment they received.
Keywords: Attitude; Elderly; Girl child education; Nutrition; Health care